ESTABLISHMENT OF HUMAN INDIGENOUS BACTERIA IN GERM-FREE MICE - Gibbons, R. J. (1964)
Gibbons, R. J. (Forsyth Dental Center and Harvard School of Dental Medicine, Boston, Mass.), S. S. Socransky, and B. Kapsimalis. Establishment of human indigenous bacteria in germ-free mice. J. Bacteriol. 88:1316–1323. 1964.—Thirteen strains of bacteria indigenous to the gingival crevice area of man were tested for their ability to establish as monocontaminants in germ-free mice. Three facultative organisms, Streptococcus mitis, Staphylococcus albus, and a “diphtheroid,” established, as well as three anaerobes. Fusobacterium fusiforme, an anaerobic diphtheroid, and a Bacteroides strain. Seven other anaerobes (two strains of B. melaninogenicus, and one strain each of Treponema microdentium, Veillonella alcalescens, a Peptostreptococcus strain, Vibrio sputorum, and B. oralis) failed to establish. A mixture consisting of ten organisms representative of the predominant groups of cultivable bacteria present in the gingival crevice area of man was inoculated intraorally into germ-free mice. All organisms with the exception of B. melaninogenicus and T. microdentium became established as polycontaminants. Escherichia coli could be established in the above polycontaminated mice, as well as in those contaminated directly with human gingival debris. E. coli comprised approximately 50 and 6% of the fecal flora in the two groups, respectively. Diet, cecal contents, and feces of germ-free and polycontaminated mice were tested for inhibitory action against T. microdentium and B. melaninogenicus. None inhibited T. microdentium, whereas all three inhibited B. melaninogenicus. The inhibitory effect appeared to be due to dietary alfalfa. B. melaninogenicus could become established in mice monocontaminated with a facultative diptheroid and maintained on an alfalfa-free diet. These experiments indicate that human indigenous bacteria can become established in germ-free mice, and that microbial interactions and diet composition are important determinants.